2017
DOI: 10.1149/07801.3077ecst
|View full text |Cite
|
Sign up to set email alerts
|

Thermoneutral Operation of Solid Oxide Electrolysis Cells in Potentiostatic Mode

Abstract: High temperature electrolysis based on solid oxide electrolysis cells (SOECs) is a promising technology for energy storage and synthetic fuel production. In recent years extensive efforts have been devoted to improving performance and durability of SOEC cells and stacks. Due to historical reasons and the convenience of doing constant current tests, (almost) all the reported SOEC tests have been galvanostatic. In this work, we report test results on two types of SOEC cells operated for electrolysis of steam in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…The inlet side is supposed to be exposed to highest value of local current density which can contribute to a faster degradation. Chen et al [38] simulated the current density distribution in the cell in the direction of the steam flow for two cells with different oxygen electrodes, the average current density of the two cells was ~ 0.9 and ~ 1.2 A/cm 2 , respectively [38]. The differences between inlet and outlet in current density were ~ 0.19 and ~ 0.35 A/cm 2 , for the two cells respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inlet side is supposed to be exposed to highest value of local current density which can contribute to a faster degradation. Chen et al [38] simulated the current density distribution in the cell in the direction of the steam flow for two cells with different oxygen electrodes, the average current density of the two cells was ~ 0.9 and ~ 1.2 A/cm 2 , respectively [38]. The differences between inlet and outlet in current density were ~ 0.19 and ~ 0.35 A/cm 2 , for the two cells respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While similar nickel depletion in the active electrode can be detected at the inlet and outlet side of the cell, a more pronounced TPB length decrease is observed at the inlet side when compared to the outlet. This effect is presumably linked with an effect of the local polarization, which is much larger at the inlet compared to the outlet (the total cell overpotential was estimated to be ~ 420 mV at the inlet and ~ 320 mV at the outlet) resulting also in a higher local current density [38]. The same trend obtained in the cell analyzed in this study was qualitatively observed in the ~ 700 hours tested cells in reference [39], where 2D low voltage SEM images showed a lower percolation degree at the inlet side.…”
Section: Overall Phase Fractions Of the Fuel Electrodementioning
confidence: 99%
“…The electrochemical durability testing of the cells was carried out at 750 °C in co‐electrolysis mode with 65% H 2 O+ 25% CO 2 + 10% H 2 in the fuel feed corresponding to a theoretic thermodynamic equilibrium composition of 23% CO 2 + 2% CO + 8% H 2 + 67% H 2 O. The voltage was kept constant at 1.2 V, with varying current densities throughout the durability testing, as a consequence of degradation . Cell A and Cell‐C were tested for 1,000 h, while Cell B for 500 h. Analysis of the impedance data was performed using the software Ravdav .…”
Section: Methodsmentioning
confidence: 99%
“…There are several advantages of doing so. First of all, the SOE can be operated in a different operating mode, that is, the thermal‐neutral or endothermic mode, with a higher utilization factor of the stack . Hence, the costly investment for the SOE is reduced.…”
Section: Process Designmentioning
confidence: 99%